2006
DOI: 10.1590/s0100-41582006000300019
|View full text |Cite
|
Sign up to set email alerts
|

First report of Tomato severe rugose virus infecting pepper plants in Brazil

Abstract: RESUMO Primeiro relato do Tomato severe rugose virus infectando plantas de pimentão no BrasilEste trabalho relata a primeira ocorrência do Tomato severe rugose virus (ToSRV) em plantas de pimentão (Capsicum annum) no Brasil. O vírus foi detectado em plantas coletadas nos municípios de Paranapanema e Piraju, São Paulo. O ToSRV é um begomovírus típico, descrito originalmente em plantas de tomateiro (Lycopersicon esculentum) e até o presente não havia sido detectado em pimentão.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…Ribeiro and co-authors (2003) also linked the emergence of new begomoviruses in tomato plantings in Brazil to the introduction of B biotype B. tabaci in the early 1990s. The other begomovirus of tomatoes in Brazil is Tomato severe rugose virus (ToSRV), which seems to be more adapted to species of Capsicum than tomato (Bezerra-Agasie et al 2006;Nozaki et al 2006). Ribeiro et al (2006) recognized that ToYVSV and PDMV are the same begomovirus, but conclude that "potato deforming mosaic disease" is caused by an isolate of ToYVSV.…”
Section: South Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Ribeiro and co-authors (2003) also linked the emergence of new begomoviruses in tomato plantings in Brazil to the introduction of B biotype B. tabaci in the early 1990s. The other begomovirus of tomatoes in Brazil is Tomato severe rugose virus (ToSRV), which seems to be more adapted to species of Capsicum than tomato (Bezerra-Agasie et al 2006;Nozaki et al 2006). Ribeiro et al (2006) recognized that ToYVSV and PDMV are the same begomovirus, but conclude that "potato deforming mosaic disease" is caused by an isolate of ToYVSV.…”
Section: South Americamentioning
confidence: 99%
“…Recently, a yellow mosaic and foliar distortion of chilli peppers (C. baccatum) observed in the states of Goias and São Paulo, Brazil [was shown to be induced] by ToSRV (Bezerra-Agasie et al 2006;Nozaki et al 2006). …”
Section: Sweet and Hot Peppersmentioning
confidence: 99%
“…Until now only ToSRV and Tomato yellow vein streak virus (ToYVSV) have been found infecting Capsicum spp. in this country (Nozaki et al, 2006). Plants of Capsicum infected by ToSRV show yellow mosaic and leaf distortion (Bezerra et al, 2006), yellowing of veins, chlorotic mottling and reduction of plant growth (Rocha et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report of begomoviruses in pepper in Brazil (Lima et al, 2001), B. tabaci belonging to the Middle East-Asia Minor 1 group, which includes the invasive populations of the commonly known B biotype (Dinsdale et al, 2010), has been frequently found in this crop, contributing to an increase in the incidence of these viruses, especially Tomato severe rugose virus (ToSRV), prevalent in São Paulo state (Nozaki et al, 2006;Rocha et al, 2010;Rocha et al, 2011) and widespread in Brazil (Fernandes et al, 2008). Brazil is considered one of the major diversity centers of the neotropical bipartite begomovirus cluster (Fernandes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Além do tomateiro, ToSRV foi relatado em cultivos de batata (Souza-Dias et al, 2008), pimenta "dedo-de-moça" (Bezerra-Agasie et al, 2006) e pimentão, no estado de São Paulo (Rocha et al, 2012;Nozaki et al, 2006). Este begomovírus também pode ser encontrado infectando naturalmente plantas daninhas, tal como Nicandra physaloides (L.), conhecida popularmente como juá-de-capote (Barbosa et al, 2009).…”
Section: Introdução Geralunclassified